IJTIHAD SAINTIFIK MODERN MAZHAB NAHDLATUL ULAMA - Sakirman, Sakirman (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2016)
The relationship between nash (text) and al-waqi' (the fact) both are territories that if mated will bring up a deeper understanding of komprehensip. The pattern in the text read according to ash-Syatibi there are three i.e. qira'ah salafiyyah qira'ah, ta'wiliyyah, and maqashidiyyah qira'ah. While in the area of al-waqi ' there are some disciplines that are used in understanding the phenomenon of social, political and other areas such as sociology, anthropology, and so on. Thus ideally when doing a reading of the text that is associated with the social phenomena should not leave the existing disciplines on the al-Waqi '. If not then an understanding of the text is out of date, so no aplicable. Thus ijtihad should always digelorakan and the door of ijtihad never closed. In this context, the science of ijtihad raiseth Usul Fiqh is a standard methodology has proved its role by Islamic thinkers like the priest sect in Islamic law, and digging in the field to the other, from the original sources (Qur'an and as-Sunnah). But nowadays the Islamic fiqh is considered barren because of the role of the framework teoritik the science of Usul fiqh is considered less relevant again to respond to contemporary problems. Then simply grounded if it appears a lot of bids for a new methodology of contemporary Islamic scholars in an attempt to dig out the original source of Islamic law to be adapted to the dynamics of the times. This fact can not be denied because the phenomenon of the global arrogance of modernity and industrialization has been menghegemoni the whole line of the lives of human beings so as to trigger the dynamics of contemporary Islam by all perangkat-perangkatnya including methodology Usul Fiqh (qawaid ushuliyah) methodology and the understanding of Fiqh (Fiqhiyyahi al-qawaid). This is a big job to be done in order to build the Islamic ideals of self (self image of Islam) in the midst of modern life that is constantly changing and evolving. In Indonesia over the past decades has appeared the development thinking of Islamic law that is adapted to the real conditions of life in Indonesia. This is effected by the realization that classical fiqh with the device its methodology have been unable to answer the question.